Free-Standing Ambulatory Surgery Centers and Hospital Surgery Volume - John Bian; Michael A. Morrisey (SAGE Publishing, 2007)
This paper examines the association of free-standing ambulatory surgery centers (ASCs) with hospital surgery volume, using data from the 2002 Medicare Online Survey Certification and Reporting System and the American Hospital Association Annual Surveys of Hospitals. From 1993 to 2001, the number of ASCs per 100,000 population in metropolitan statistical areas (MSAs) increased by 150%. During the same period, hospital outpatient surgeries increased 28%, while inpatient surgeries decreased by 4.5%. MSA and year fixed-effects regression analyses suggest that an increase of one ASC per 100,000 people was associated with a 4.3% reduction in hospital outpatient surgical volume, but was not associated with inpatient surgical volume.